CORRELATION BETWEEN LIFESTYLE AND HYPERTENSION INCIDENCE AT THE WERDHI AGUNG PUBLIC HEALTH CENTRE IN BOLAANG MONGONDOW REGENCY - Runturambi, Citari; Priasmoro, Dian Pitaloka (Jurnal Penelitian Keperawatan Kontemporer, 2026)
Background: Hypertension, or high blood pressure, is a global health problem and a major risk factor for cardiovascular disease. The incidence of hypertension is greatly influenced by lifestyle factors, including diet, physical activity, smoking, and stress. Optimal management requires a thorough understanding of these risk factors. Objective: Analyzing the relationship between lifestyle and hypertension in the working area of the Werdhi Agung Community Health Center in Bolaang Mongondow Regency. Methods: This study used a cross-sectional design with the population and sample consisting of patients treated at the Werdhi Agung Community Health Center. The sample size was planned to be 70 respondents, selected using consecutive sampling. Data were collected using a structured questionnaire on lifestyle and medical records for hypertension status. Statistical analysis will use the Chi-Square test with a significance level of 95% (α=0.05). Results: The univariate analysis results show that the majority of respondents have a Healthy Lifestyle (80.0%) and the majority experience Hypertension (68.6%). The bivariate statistical test yielded a P value of 0.000 or P < 0.05, indicating a significant relationship between lifestyle and hypertension. However, in terms of frequency, hypertension was more prevalent in the “Good” lifestyle group (48 respondents; 68.6%), while there were no cases of hypertension in the “Poor” lifestyle group. Conclusion: There is a statistically significant relationship between lifestyle and the incidence of hypertension. The counterintuitive findings indicate that non-modifiable risk factors such as advanced age (> 65 years) or a history of long-term exposure to risk play a strong role, or that there is a need to re-examine the lifestyle measurement instruments used